The magnitude of precancerous cervical lesions and its associated factors among women screened for cervical cancer at a referral center in southern Ethiopia, 2021: a cross-sectional study - Tenkir, Lidiya; Mamuye, Abyalew; Jemebere, Wegene; Yeheyis, Tomas (Frontiers in Global Women's Health, 2023)
Background: cervical cancer is the most prevalent gynecologic cancer in women and the second leading cause of cancer death worldwide. Africa's southern, eastern, and western regions have the greatest rates of cervical cancer. Cervical cancer is treatable and curable when detected early, but it is nonetheless fatal in low-and middle-income (LMIC) nations where screening and early detection are not widely accessible.Objective: The objective of this study is to assess the magnitude of precancerous cervical lesions and its associated factor among women screened for cervical cancer at a referral center in southern Ethiopia, in 2021.Methods: A retrospective institution-based cross-sectional study was conducted from February 21 to April 14, 2022, among randomly selected 372 records of women screened for cervical cancer at Hawassa University Specialized Hospital. Data was extracted from clients' charts using a data extraction checklist. Statistical Package for Social sciences version 26, and logistic regression analysis were applied to determine the association between dependent and independent variables, and significance was declared at p-value <0.05.The magnitude of abnormal cervical dysplasia in this study was 18,3% of which 14% were precancerous cervical lesions and 4,3%were cervical cancer. Early coitarche; Adjusted Odds Ratio (AOR) = 5.6 [95 %( Confidence Interval) CI= 1.87-16.78], having more than one sexual partner; AOR = 2.6 [95%CI = 1.2-5.68], being HIV positive; AOR = 3.56 [95%CI = 1.53-8.29], and having sexually transmitted infections; were independent predictors of precancerous cervical lesions.The magnitude of precancerous cervical lesions in the study setting is 18% and the magnitude of cervical cancer is 14%, which is higher than the pooled prevalence of precancerous cervical lesions in Ethiopia. Having multiple sexual partners, being HIV positive, having sexual intercourse before 21 years, and new STI diagnosis was independently associated with abnormal precancerous cervical lesions.